HUBUNGAN KEKUATAN OTOT EKSTREMITAS BAWAH TERHADAP RISIKO JATUH PADA LANJUT USIA - sabela maulida; Muthiah Munawwarah; Jerry Maratis; Abdul Chalik Meidian (Jurnal Ilmiah Fisioterapi, 2025)
ABSTRACT Objective: To determine the relationship between lower extremity muscle strength and fall risk in elderly people aged 60-75 years. Method: This study used a quantitative cross-sectional approach. The sample consisted of 41 elderly people from Kalimati Village, RT 011 RW 003, Kedaung Kaliangke, Cengkareng, West Jakarta. The study will examine the correlation between lower extremity muscle strength and fall risk using the Five-Time Sit-to-Stand Test (FTSST) and the Timed Up-and-Go Test (TUGT) simultaneously to determine the relationship between lower extremity muscle strength and fall risk. Results: The Shapiro-Wilk test for normality found that the data were normally distributed, with a mean ± SD value for the FTSST of 9.74±2.30 and a mean ± SD value for the TUGT of 9.69±2.56. The person correlation test was used to test the hypothesis, with a p-value <0.001 indicating a significant relationship between lower extremity muscle strength and the risk of falls in the elderly. The correlation coefficient (r=0.868) indicates a relationship between lower extremity muscle strength and the risk of falls in the elderly. Conclusion: There was a relationship between lower extremity muscle strength and the risk of falls in the elderly.